Implementation Of Syuf'ah & As-Sharf Service Agreement In Modern Digitalization With Shariah Concept - Cica Nur Sabila; Dinda Paramudia; Muhammad Nur Iqbal (Jurnal Multidisiplin Sahombu, 2025)
Research This analyze draft syuf'ah and al- sharf in law jurisprudence transactions , with focus on the underlying conditions and principles practice both of them in Islamic economics . Syuf'ah is right long time partner in partnership For buy return assets for sale to party third , while al- sharf related with transaction exchange foreign currency . Using​ approach descriptive-analytical , research This dig source Islamic law and the opinions of scholars for evaluate conformity practice This in context economy contemporary . Methodology research used​ in study This is study qualitative that is law normative in which will process a number of source of data taken from various source , Research results show that second transaction emphasize on the principle justice , transparency and certainty law . The conditions set , such as: transaction cash and without delay , must fulfilled to be valid according to sharia. Research This conclude that both of them must applied with notice sharia principles for guard legitimacy and welfare in practice Islamic economics .